Control Rights, Debt Structure, and the Loss of Private Benefits: The Case of the UK Insolvency Code - Franks, Julian R.; Nyborg, Kjell G. (Review of Financial Studies, 1996)
We show how the efficiency of reorganization is affected by the distribution of control rights under the U.K. insolvency code. Control rights raise particular problems when creditors have different incentives to keep the firm as a going concern. Such differences may arise from the possession of private benefits by particular creditors which are lost if the debtor firm is liquidated. The incidence of inefficient liquidations is influenced by the size and seniority of creditors’ claims. The current U.K. code is widely thought to give rise to inefficient liquidations. We show, however, that inefficiency depends upon the debt structure and whether the controlling creditor in formal bankruptcy has private benefits.